Neurological presentation of Wilson’s disease without overt hepatic involvement - Arora, Sunita; Kaur, Arshpuneet (International Journal of Contemporary Pediatrics, 2021)
Wilson disease (hepatolenticular degeneration) is a rare autosomal recessive disease. Here, we report a child affected by Wilson disease with only neurological manifestations without hepatic involvement.